(untitled) (Bangladesh Journal of Pharmacology, 2015)
Three Actinomyctes with potential bioactivity are successfully isolated from the marine water samples and identified as Prauserella marina, Streptomyces sindenensis and S. spiroverticillatus. The ethyl acetate extracts from the three Actinomycetes are found to have significant bioactivity. The highest anti-bacterial activity was given by the extract from P. marina on B. cereus showing 28 mm of zone of inhibition. Cytotoxicity screening of the crude extracts using 3-(4, 5-dimethylthiazol-2yl)-2, 5-diphenyl tetrazolium bromide (MTT) cell viability assay revealed that extract from P. marina noticeably effected the viability of the human cervical cancer cell grown in vitro. Thin layer chromatography of the crude extract with methanol and chloroform (8:2) as solvent system yielded three distinct fractions, of which fraction with Rf value 0.8 resulted in 77, 68, 54 and 40% growth inhibition of HeLa cells at 15, 10, 5, 2.5 µg/mL, respectively with the IC50 value as 3.3 µg/mL. HPLC analysis of the fraction resulted in single major peak at 3.7 min.